MENENTUKAN PREMI TAHUNAN UNTUK TIGA ORANG PADA ASURANSI JIWA HIDUP GABUNGAN (JOINT LIFE) - BHUANA, TRI YANA; WIDANA, I NYOMAN; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 4 No 4 (2015)DO - 10.24843/MTK.2015.v04.i04.p111, 2015)
Life insurance products consist of a single life insurance and joint life insurance. Joint life is a state where the rule die life is a combination of two or more factors, such as the husband-wife, parent-child . T he research is to obtain the formula of the annual premium of joint life insurance with the age of x, y, and z. By using formula and constants Helligmann-Pollard will be determined value of mortality tables, life annuity and single premium to get the formula annual premium joint life insurance for three persons. In addition, this study also aims to get the number of annual premium joint life insurance for a household of three consisting of a married couple and one son with the ages of 50, 45, dan 15 years old, with the interest rate of 5% used. For the contract terms of one and two years, the annual premium of joint life for two persons respectively and greater than the joint life insurance of three persons. While for three to ten years contract, the annual premium of joint life insurance three person is bigger than the joint life insurance for two persons.
Keywords: Joint Life Insurance, Annual Premium Two Person, Annual Premium Three Person